Effect of Light Intensity and Light Quality on Diatom Behavioral and Physiological Photoprotection - Prins, Antoine; Deleris, Paul; Hubas, Cédric; Jesus, Bruno (Frontiers in Marine Science, 2020)
In this study, we investigated the different photoregulation responses of diatom dominated natural biofilms to different light intensities and wavelengths, over a tidal cycle in the laboratory. We compared the overall effect of light spectral quality from its light absorption (Qphar) dependent effect. Two different conditions were compared to study photoprotective strategies: sediment (migrational) and without sediment (non-migrational). Three different colors (blue, green and red) and two light intensities (low light, LL at 210 μmol.photons.m-2.s-1and high light, HL at 800 μmol.photons.m-2.s-1) showed strong interactions in inducing behavioral and physiological photoprotection. Non-migrational biofilm non-photochemical quenching (NPQ) was much more reactive to blue HL than red HL while it did not differ in LL. We observed a biphasic NPQ response with a light threshold between 200 and 250 μmol.photons.m-2.s-1 of Qphar that elicited the onset of physiological photoprotection. Similar HL differences were not observed in migrational biofilms due to active vertical migration movements that compensated light saturating effects. Our results showed that within migrational biofilms there was an interaction between light quality and light intensity on cell accumulation pattern at the sediment surface. This interaction led to inverse diatom accumulation patterns between blue and red light at the same intensity: LL (blue +200.67%, red +123.96%), HL (blue +109.15%, red +150.34%). These differences were largely related to the differential amount of light absorbed at different wavelengths and highlighted the importance of using wavelength standardized intensities. Different vertical migration patterns significantly affected the total pigment content measured at the surface, suggesting that cell could migrate downward more than 2mm as a photoregulatory response. Colloidal carbohydrates patterns paralleled the vertical migration movements, highlighting their possible role in diatom motility. Our data strongly suggests a wavelength and Qphar dependent light stress threshold that triggers upward and downward movements to position microphytobenthic diatoms at their optimal depth.